Saltwater Intrusion and Submarine Groundwater Discharge: Acceleration of Biogeochemical Reactions in Changing Coastal Aquifers - Moore, Willard S.; Joye, Samantha B. (Frontiers in Earth Science, 2021)
Intrusion of saltwater into freshwater coastal aquifers poisons an essential resource. Such intrusions are occurring along coastlines worldwide due largely to the over-pumping of freshwater and sea level rise. Saltwater intrusion impacts drinking water, agriculture and industry, and causes profound changes in the biogeochemistry of the affected aquifers, the dynamic systems called subterranean estuaries. Subterranean estuaries receive freshwater from land and saltwater from the ocean and expose this fluid mixture to intense biogeochemical dynamics as it interacts with the aquifer and aquiclude solids. Increased saltwater intrusion alters the ionic strength and oxidative capacity of these systems, resulting in elevated concentrations of certain chemical species in the groundwater, which flows from subterranean estuaries into the ocean as submarine groundwater discharge (SGD). These highly altered fluids are enriched in nutrients, carbon, trace gases, sulfide, metals, and radionuclides. Seawater intrusion expands the subterranean estuary. Climate change amplifies sea level variations on short and seasonal time scales. These changes may result in higher SGD fluxes, further accelerating release of nutrients and thus promoting biological productivity in nutrient-depleted waters. But this process may also adversely affect the environment and alter the local ecology. Research on saltwater intrusion and SGD has largely been undertaken by different groups. We demonstrate that these two processes are linked in ways that neither group has articulated effectively to date.